2011
DOI: 10.1099/ijs.0.023317-0
|View full text |Cite
|
Sign up to set email alerts
|

Candida saraburiensis sp. nov. and Candida prachuapensis sp. nov., xylose-utilizing yeast species isolated in Thailand

Abstract: Four strains of two novel xylose-utilizing yeast species were obtained from samples collected in Thailand from decaying corncobs (strains KU-Xs13T and KU-Xs18), a decaying grass (KU-Xs20) and estuarine water from a mangrove forest (WB15T). On the basis of morphological, biochemical, physiological and chemotaxonomic characteristics and sequence analysis of the D1/D2 domain of the large subunit rRNA gene, the four strains were found to represent two novel species of the genus Candida in the Candida albicans/Lodd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…T. asahii have a medical association, being commonly found as the causative agent of disseminated mycoses in patients with impaired immunity, and occasionally as the cause of human or animal white piedra (28). S. lactativora strains appear to be cosmopolitan in distribution, such as in soil, fermented food, decaying agriculture residue and bird feces in Antarctica (9, 24, 31), and they could grow at high temperatures of 37°C or more (37). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T. asahii have a medical association, being commonly found as the causative agent of disseminated mycoses in patients with impaired immunity, and occasionally as the cause of human or animal white piedra (28). S. lactativora strains appear to be cosmopolitan in distribution, such as in soil, fermented food, decaying agriculture residue and bird feces in Antarctica (9, 24, 31), and they could grow at high temperatures of 37°C or more (37). …”
Section: Resultsmentioning
confidence: 99%
“…S. arborariae strain from rotting wood in Brazil was reported to produce ethanol (0.50 g g −1 xylose) (5) and Candida saraburiensis from decaying agriculture residue produced ethanol (3.1–3.6 g L −1 at 72 h) (31). Spathaspora passalidrum from the gut of passalid beetles could produce ethanol (0.4 g g −1 xylose) (13), and C. guilliermondii Xu280, C. maltosa Xu316 and strain YS54 could produce xylitol 0.73 g g −1 , 0.70 g g −1 and 0.58 g g −1 , respectively (12, 35).…”
Section: Ethanol and Xylitol Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The clade includes an additional 30 anamorphic Candida species, among them the major human pathogens Candida albicans, Candida dubliniensis, Candida parapsilosis, Candida metapsilosis, Candida orthopsilosis, and Candida tropicalis (Lachance et al 2011a). Members of the clade were isolated from various sources, such as marine habitats, food, plants, and soil (Lachance et al 2011;Nitiyon et al 2011;Nakase et al 2009;Limtong et al 2012;Sipicszki 2013), soft drinks (Chang et al 2012), and human and animals (Weems 1991;Wingard 1995;Trofa et al 2008;Cooper 2011;Kim & Sudbery 2011;Lachance et al 2011a). Studies conducted in different geographic regions showed that insects frequently host yeasts belonging to the Lodderomyces clade, including the human pathogens (Nguyen et al 2007;Suh et al 2008;Ji et al 2009, Urbina 2012.…”
Section: Introductionmentioning
confidence: 98%
“…Saccharomyces cerevisiae is the most popular yeast for fermenting glucose to ethanol due to its high ethanol production yield and comparatively high ethanol tolerance 4,5 , however S. cerevisiae strains cannot ferment xylose to ethanol. Several yeasts such as Candida shehatae, Pachysolen tannophilus, Brettanomyces naardenensis, C. tenuis, Pichia segobiensis, C. lyxosophila, C. intermedia, C. jeffriesii, Spathaspora passalidarum, Spathaspora arborariae, C. prachuapensis, and Scheffersomyces stipitis have been reported as xylose fermenting yeasts [6][7][8][9][10] . The S. stipitis strain produces significant amounts of ethanol from xylose and it has been studied extensively 9 .…”
Section: Introductionmentioning
confidence: 99%